A celebration of the artists (Notes on Balzac’s article “On Artists”) - S. N. Zenkin (Шаги, 2024)
The article provides historical comments to Honoré de Balzac’s article “Des artistes” (1830). It shows the genre complexity of the text, which references the traditions of the rhetorical panegyric, the literary and artistic manifesto and the physiological essay that describes a certain social “type”. The title word “artistes” gets a new, expanded meaning, including in the category of “men of art” also writers and connoisseurs of beauty; this semantic evolution was prepared by the writings of the French Saint-Simonists. The man of art is considered by Balzac not only in the process of creativity, but also in the course of “artistic life”; in this regard, the connection between writers and artists reflected the real cultural changes of the early 1830s, the formation of the “Jeunes-France” subculture which united young painters and poets, admirers of the new Romantic literature. Aiming to affirm the dignity of the men of letters and, more specifically, to obtain a fair remuneration for literary work in the epoch of autonomization of the literary field, Balzac uses the rhetoric of “inspiration” but at the end is forced to call on “artists” to stoically suffer their marginality: this is his interpretation (seemingly the first in print) of the famous slogan “Art for Art’s Sake”.